2004
DOI: 10.1530/eje.0.1500877
|View full text |Cite
|
Sign up to set email alerts
|

Identification of amino-acids in the alpha-subunit first and third loops that are crucial for the heterospecific follicle-stimulating hormone activity of equid luteinizing hormone/choriogonadotropin

Abstract: Identification of amino-acids in the a-subunit first and third loops that are crucial for the heterospecific follicle-stimulating hormone activity of equid luteinizing hormone/choriogonadotropin M Chopineau, N Martinat, J F Gibrat 1 , C Galet, F Lecompte, F Foulon-Gauze, C Pourchet, F Guillou and Y Combarnous AbstractObjective: To identify amino-acids in the a-subunit important for expression of heterospecific FSH activity of horse (e) LH/choriogonadotropin (CG) (eLH) and donkey (dk) LH/CG (dkLH) (FSH/LH rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…rat FSHR and LHR, as summarized in the SSFA-GPHR and GRIS servers (Kleinau et al, 2007;Van Durme et al, 2006), combinations of a and b subunits for horse and donkey CG and FSH (Chopineau et al, 2004), duck FSH (Shen et al, 2006), horse TSHR (Royer et al, 2008) and the LH and FSH b subunits of snakehead fish (Chatterjee et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…rat FSHR and LHR, as summarized in the SSFA-GPHR and GRIS servers (Kleinau et al, 2007;Van Durme et al, 2006), combinations of a and b subunits for horse and donkey CG and FSH (Chopineau et al, 2004), duck FSH (Shen et al, 2006), horse TSHR (Royer et al, 2008) and the LH and FSH b subunits of snakehead fish (Chatterjee et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Many workers across the globe reported the studies on alpha-subunit of pituitary glycoprotein hormones. Chopineau et al (2004), reported the identification of aminoacids in the alpha-subunit first and third loops, that are crucial for the hetero-specific follicle-stimulating hormone activity of equid luteinizing hormone/gonadotropin. It was precisely shown that which amino-acids of the alpha-subunit are implicated in the interaction with gonadotropin receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies, including the presented one, focus on the b subunit of equine gonadotropic hormones, the a subunit has been shown to play a crucial role for the biological activity of the dimeric molecule (Papkoff 1974, Chopineau et al 1997, 2004. Wolkersdörfer et al (1998) suggested a circulating pool of free a subunits in women, being systemically available due to an excessive secretion into the blood stream by the pituitary gland (Hagen et al 1976).…”
Section: Discussionmentioning
confidence: 99%